Impact of land use change to the soil erosion estimation for cultural landscapes: case study of Paphos disrict in Cyprus - Cuca, Branka; Agapiou, Athos (My University, 2017)
In 2006 UNESCO report has identified soil loss as one of the main threats of climate change with possible impact to natural and cultural heritage. The study illustrated in this paper shows the results from geomatic perspective, applying an interdisciplinary approach undertaken in order to identify major natural hazards affecting cultural landscapes and archaeological heritage in rural areas in Cyprus. In particular, Earth Observation (EO) and ground-based methods were identified and applied for mapping, monitoring and estimation of the possible soil loss caused by soil erosion. Special attention was given to the land use/land cover factor (C) and its impact on the overall estimation of the soil-loss. Cover factor represents the effect of soil-disturbing activities, plants, crop sequence and productivity level, soil cover and subsurface bio-mass on soil erosion. Urban areas have a definite role in retarding the recharge process, leading to increased runoff and soil loss in the broader area. On the other hand, natural vegetation plays a predominant role in reducing water erosion. The land use change was estimated based on the difference of the NDVI value between Landsat 5 TM and Sentinel-2 data for the period between 1980s' until today. Cover factor was then estimated for both periods and significant land use changes were further examined in areas of significant cultural and natural landscape value. The results were then compared in order to study the impact of land use change on the soil erosion and hence on the soil loss rate in the selected areas.
Keywords: Cultural landscapes; Earth observation; GIS; Land use change; RUSLE/USLE; Satellite remote sensing; Soil erosion